2017
DOI: 10.1080/03639045.2017.1414229
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and ex vivoin vivo evaluation of pH-triggered brimonidine tartrate in situ gel for the glaucoma treatment using application of 32 factorial design

Abstract: The developed in situ gelling system as a promising ophthalmic formulation to prolong the drug lowering effect on the intraocular pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…Brimonidine tartrate (BRT) is a hydrophilic drug used for treatment of glaucoma, its pharmacological classification is α 2 adrenergic agonist acts by dual mechanisms, decreasing aqueous humor production and increasing the uveoscleral outflow as it promotes prostaglandins synthesis, it has a neuroprotective action and decrease the ischemia-induced optic nerve damage (Saylor et al., 2009; Barse et al., 2018). Moreover, it has the advantage of being effective in normal tension glaucoma (Gandolfi et al., 2003), where IOP measurements are below 21 mm Hg but characteristic glaucomatous structural and functional optic nerve defects are present (Razeghinejad & Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Brimonidine tartrate (BRT) is a hydrophilic drug used for treatment of glaucoma, its pharmacological classification is α 2 adrenergic agonist acts by dual mechanisms, decreasing aqueous humor production and increasing the uveoscleral outflow as it promotes prostaglandins synthesis, it has a neuroprotective action and decrease the ischemia-induced optic nerve damage (Saylor et al., 2009; Barse et al., 2018). Moreover, it has the advantage of being effective in normal tension glaucoma (Gandolfi et al., 2003), where IOP measurements are below 21 mm Hg but characteristic glaucomatous structural and functional optic nerve defects are present (Razeghinejad & Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both in vitro and in vivo tests indicated that the hybrid hydrogel displayed the superior precorneal retention of drugs over the Carbopol or Pluronic aqueous solution alone. A similar ophthalmic drug delivery system was also reported by Barse and coworkers, who used Carbopol in combination with hydroxypropyl methylcellulose (HPMC) for topical glaucoma treatment . Experimental results demonstrated that the optimized hybrid hydrogel could provide a relatively long‐term duration of drug action and improve IOP reduction activity compared to marketed eye drops in the in vivo study.…”
Section: Ophthalmic Hydrogel Systemmentioning
confidence: 60%
“…It was observed after administration of marketed eye drop formulation, the rapid reduction in intraocular pressure upto 3 h, but due to liquid nature of formulation it had no ability to retain in cul de sac region. The results showed that after 3 h % decrease in IOP again decrease in case of marketed formulation due to its liquid nature [47,[48][49][50].…”
Section: G In Vivo Studiesmentioning
confidence: 99%